YAKIV ORENSTEIN: AN EXPATRIATED UKRAINOPHIL FROM GALICIA - MONOLATII, IVAN (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
Ukrainian-Jewish relations in Galicia between the two World Wars were the reflection of the difference in the status of the two nations. The sides failed to come to mutual understanding, the basis for which was provided by the policy of the West Ukrainian People’s Republic / the Western Oblast of the Ukrainian People’s Republic. Taking into account the involvement of the third party, the Polish state, the situation can be described as an interethnic scalene triangle. One of the active figures in this complicated interaction was Yakiv Orenstein (1875–1942), Jewish publisher from Kolomyia, symbolic ‘Ukrainian’, follower of the faith of Moses. His life and work in Galicia in the interwar years is a personalized example of publicly declared pro-Polishness and actual Ukrainophilia.